Sex-specific associations between sleep apnoea and lung cancer risk in patients with COPD: a nationwide prospective cohort studyResearch in context - Kristiaan Proesmans; Annemarie I. Luik; Lies Lahousse (The Lancet Regional Health. Europe)
Summary: Background: COPD is an established risk factor for lung cancer. Sleep apnoea is prevalent in COPD and the inflammation caused by intermittent hypoxaemia may increase this lung cancer risk. Females have more systemic inflammation for a similar apnoea-hypopnoea index than males. Therefore, this study aims to investigate sex-specific associations between sleep apnoea and lung cancer in COPD. Methods: The sex-specific absolute and relative risk of sleep apnoea on newly diagnosed lung cancer was estimated in a nationwide observational study of Belgian patients with COPD (≥55 years), between 2017 and 2022, using an Aalan-Johanson estimator and a cause-specific Cox regression model adjusted for age, socioeconomic status, smoking status, alcoholism, frailty, comorbidities, and comedication. Findings: The study consisted of 62,903 COPD patients (42·80% female), of whom 2898 (4·60%) developed lung cancer. We found a significant sex interaction of sleep apnoea on lung cancer hazard (χ-squared: 13·239, P-interaction < 0·01). In females, sleep apnoea was associated with a higher lung cancer risk (cumulative incidence: 1545 vs 1350 per 100,000 PY; aHR: 1·31 (95% CI: 1·05–1·63)). For males, sleep apnoea patients had a lower lung cancer risk (cumulative incidence: 1632 and 2305 per 100,000 PY; aHR: 0·82 (95% CI: 0·70–0·95)). The impact of sleep apnoea on lung cancer development was especially strong in female COPD patients with hypoxia-related comorbidities e.g., with a history of emphysema (aHR: 2·65 (95% CI: 1·11–6·34)). Interpretation: Sleep apnoea was associated with a higher risk of lung cancer in female COPD patients while, in males, there was a lower risk. Especially in female COPD patients with hypoxia, sleep apnoea is strongly associated with an increased lung cancer risk. Funding: Emmanuel van der Schueren cancer research fellowship “Kom Op Tegen Kanker”.